Engaging with Patients, Families and Caregivers to Support Ontario Health Teams - Gauvin, François-Pierre; Waddell, K; Dion, A; Lavis, JN; Abelson, J; Bullock, H (My University, 2020)
An assessment of what is known about problems related to engaging with patients, families and caregivers in the context of Ontario Health Teams, options for addressing these problems, and key implementation considerations. The citizen brief was an input to a citizen panel on the topic of engaging with patients, families and caregivers to support Ontario Health Teams.
Keywords: patient; family; caregiver; Ontario Health Team